Globally smooth output feedback stabilization of a class of planar switched systems with average dwell time. (May 2017) - Li, Xueling; Lin, Xiangze; Li, Shihua; Zou, Yun
Abstract: Smooth output feedback stabilization for a family of planar switched nonlinear systems with average dwell time is addressed. Based on the adding a power integrator method, multiple Lyapunov functions are constructed and state stabilizing feedback laws are designed simultaneously. Multiple one-dimensional compensators for the switched nonlinear system whose subsystems may have uncontrollable/unobservable Jacobian linearization are constructed to estimate the unmeasurable states. Coupling the state feedback controllers with the nonlinear observers, globally asymptotical stabilization of the switched nonlinear system is achieved by output feedback controllers. The average dwell time method is used to choose switching signals. Simulation results are employed to verify the efficiency of the proposed method.